CD83 expression characterizes precursor exhausted T cell population - Zhiwen Wu; Toshiaki Yoshikawa; Satoshi Inoue; Yusuke Ito; Hitomi Kasuya; Takahiro Nakashima; Haosong Zhang; Saki Kotaka; Waki Hosoda; Shiro Suzuki; Yuki Kagoya (Communications Biology, 2023)
CD83, a member of the immunoglobulin superfamily, is a novel marker to discriminate precursor exhausted T cells from terminally exhausted and bystander tumor-infiltrating T-lymphocytes.